2013
DOI: 10.1111/apt.12271
|View full text |Cite
|
Sign up to set email alerts
|

The characterisation and risk factors of ischaemic heart disease in patients with coeliac disease

Abstract: SUMMARY BackgroundStudies have shown an increased risk of ischaemic heart disease (IHD) in patients with coeliac disease (CD), despite the patients' lack of traditional IHD risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
61
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 36 publications
4
61
0
Order By: Relevance
“…In a recent study, Emilsson et al (23) reported that patients with CD and ischemic heart disease had lower levels of classical risk factors such as obesity, smoking, and cholesterol, but systemic inflammation associated with CD could have a causative role in the increase of comorbid cardiovascular diseases seen in CD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Emilsson et al (23) reported that patients with CD and ischemic heart disease had lower levels of classical risk factors such as obesity, smoking, and cholesterol, but systemic inflammation associated with CD could have a causative role in the increase of comorbid cardiovascular diseases seen in CD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our findings are in accordance with observations in other different immune disorders. 4 As a diagnosis of CD is becoming increasingly common in the general population, we share the point of Dr Ludvigsson that cardiovascular risk pattern in CD patients needs to be thoroughly addressed. As a matter of fact, we are developing a large prospective trial to test our results and any suggestion from referral academic centres is highly appreciated.…”
mentioning
confidence: 99%
“…3,4 They conclude that young adults with coeliac disease are at increased risk of higher mean LDL cholesterol, have a thicker carotid intima media thickness (IMT), while their endothelium-dependent dilatation is decreased -all bad for cardiovascular health. Interestingly, the authors also found that dietary treatment influenced C-reactive protein levels, and that both IMT and endothelium-dependent dilatation improved with diet.…”
mentioning
confidence: 99%
“…Celiac disease has been linked to a slightly increased risk of cardiovascular disease [1]. Several studies have reported increased blood pressure but lower body mass index (BMI), improved cholesterol profiles, and fewer smokers in individuals with celiac disease [2,3]. Mucosal healing in celiac disease is not associated with a decreased risk of myocardial infarction, stroke, or atrial fibrillation when compared to celiac individuals with persistent villous atrophy [4].…”
mentioning
confidence: 99%